Final overview of COST Action TU1406 – Quality control of existing bridges - Matos, José C. (2019)
Across Europe, the need to manage roadway bridges efficiently led to the development of multiple management systems. Despite presenting similar system frameworks, the condition assessment procedure is one of the difference that distinguishes them. This dissimilarity constitutes a divergent mechanism that has direct interference in the decision making process leading to considerable variations in roadway bridges quality. COST Action TU1406 aims to institute a standardized roadway bridges condition assessment procedure. Such purpose requires the establishment of recommendations for the quantification of performance indicators, the definition of performance goals and a guideline for the standardization of quality control plans for bridges. By developing new approaches to quantify and assess bridge performance, as well as quality specifications to assure expected performance levels, bridge management strategies will be significantly improved, enhancing asset management of ageing structures in Europe. The work developed and achieved by COST Action TU1406 will be presented.